Microthrombotic Renal Vascular Lesions Are Associated to Increased Renal Inflammatory Infiltration in Murine Lupus Nephritis - Gonzalo-Gil, Elena; García-Herrero, Carmen; Toldos, Oscar; Usategui, Alicia; Criado, Gabriel; Pérez-Yagüe, Sonia; Barber, Domingo F.; Pablos, Jose L.; Galindo, Maria (Frontiers in Immunology, 2018)
Background: Vascular microthrombotic lesions in lupus nephritis with or without antiphospholipid antibodies may relate to worse renal outcomes. Whether microthrombotic lesions are a consequence of renal inflammation or independently contribute to renal damage is unclear. Our aim was to investigate the relationship between microthrombotic renal vascular lesions and nephritis progression in MRL/lpr mice. Methods: MRL/lpr mice were analyzed by the presence of renal microvascular, glomerular and tubulointerstitial lesions. Intravascular platelet aggregates (CD41), peri- (F4/80) and intraglomerular (Mac-2) macrophage infiltration, and C3 deposition were quantified by immunohistochemistry. Renal function was assessed by measuring proteinuria, and serum levels of creatinine and albumin. Anti-dsDNA and anti-cardiolipin antibodies, and thromboxane B2 levels were quantified by ELISA. The effect of anti-aggregation (aspirin or clopidogrel) and dexamethasone on renal clinical and pathological manifestations was analyzed. Results: Frequency of microthrombotic renal lesions in MRL/lpr mice was high and was associated with immune-mediated renal damage. Proteinuria positively correlated with glomerular macrophage infiltration and was higher in mice with proliferative glomerular lesions. Proteinuria and glomerular macrophage infiltration were significantly reduced in all treatment groups. All mice had detectable anti-dsDNA and anti-cardiolipin IgG, regardless the presence of microthrombosis. Dexamethasone and platelet anti-aggregation similarly reduced glomerular damage and inflammation, but only platelet anti-aggregation significantly reduced anti-cardiolipin antibodies and renal complement deposition. Conclusions: Platelet anti-aggregation reduced renal inflammatory damage, anti-cardiolipin level and renal complement deposition in MRL/lpr mice, suggesting that platelet activation has a pathogenic effect on immune-mediated nephritis. Our results point to MRL/lpr mice with lupus nephritis as an appropriate model to analyze the potential impact of anti-thrombotic intervention on renal inflammation.